Smart Spaces and Next Generation Wired/Wireless Networking 11th International Conference, NEW2AN 2011, and 4th Conference on Smart Spaces, ruSMART 2011, St. Petersburg, Russia, August 22-25, 2011. Proceedings - Balandin, Sergey; Koucheryavy, Yevgeni; Hu, Honglin; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 11th International Conference on Next Generation Teletraffic and Wired/Wireless Advanced Networking, NEW2AN 2011 and the 4th Conference on Smart Spaces, ruSMART 2011 jointly held in St. Petersburg, Russia, in August 2011. The 56 revised full papers presented were carefully reviewed and selected from numerous submissions. The ruSMART papers are organized in topical sections on role of context in smart spaces, smart spaces platforms and smart-M3, methods for studying smart spaces, and smart spaces solutions. The NEW2AN papers are organized in topical sections on wireless PHY and power control, ad hoc networks, WSN, special topics, simulation + fundamental analysis I, traffic modeling and measurement, simulation + fundamental analysis II, network performance and QoS, cooperative, P2P, overlay networks and content, applications and services, API and software, and video.
Keywords: Computer science; Computer network architectures; Computer Communication Networks; Data encryption (Computer science).; Computer software; Information systems; Telecommunication; Computer Science; Computer Communication Networks; Computer Systems Organization and Communication Networks; Data Encryption; Information Systems and Communication Service; Algorithm Analysis and Problem Complexity; Communications Engineering, Networks